Peran dan Pengelolaan Ekowisata Satwa Liar Non Penangkaran Kawasan Punggualas di Taman Nasional Sebangau Kabupaten Katingan - Fadhella, Rahmi; Kharin, Bella Des; Kefi, Putri Sion Desmy; Rahmanita, Myrza (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
The purpose of this research is to describe the role and management of non-captive wildlife ecotourism carried out in the Punggualas area of ​​Sebangau National Park, Katingan Regency. The research method used is qualitative with literature review and data obtained from journals, books, the official website of the manager. The results of the study indicate that the management and management of non-captive wildlife ecotourism in the Punggualas area of ​​Sebangau National Park, Katingan Regency is still classified as moderate and not optimal because of its role and management as a dynamist which is still managed by only one community, namely the Karuing village knot community group, the need to form an institution or other communities and synergize related parties in ecotourism management such as empowering local communities, training programs, and working with investors. As a motivator role, government support is needed in the form of outreach to the community. Furthermore, the role of this innovator is raised with the intention of utilizing technical resources that can be implemented, there is a reciprocal relationship between organisms and their environment and is accepted by society. This is to produce mutual benefits for all parties both in terms of economic, social and cultural. Keywords: Ecotourism, Non-Captive Wildlife, Role, Management